Deciphering Planktonic Bacterial Community Assembly in the Storage Reservoir of the Long-Distance Water Diversion Project - Yingying Yang; Liguo Chen; Nianxin Wan; Ailing Xu; Ning Ding; Zhiwen Song (Microorganisms)
Storage reservoirs are crucial components of long-distance water diversion projects, where water diversion may lead to changes in microbial diversity and community structure. Seasonal variations also drive alterations in microbial communities. However, the way that microbes assemble under the combined effects of water diversion and seasonal variations in the storage reservoir has not been extensively studied. Jihongtan Reservoir is the terminal storage reservoir of the Yellow River to Qingdao Water Diversion Project (YQWD), which had an average annual water diversion period exceeding 290 days in recent years. In this study, 16S rDNA amplicon sequencing was used to investigate the seasonal dynamics and assembly of planktonic bacterial communities during the water diversion period in Jihongtan Reservoir. The results indicate that planktonic bacteria were able to maintain stable diversity across all four seasons, while the community structure underwent significant seasonal succession. Water temperature (WT) was found to be the primary driving environmental factor influencing the seasonal dynamic of planktonic bacterial communities. Co-occurrence network patterns of planktonic bacterial communities varied across different seasons, particularly in spring and winter. The spring network displayed the most complexity, showcasing the highest connectivity and greater stability. In contrast, the winter network was simpler, exhibiting lower local connectivity but higher global connectivity and lower stability. The analysis of the neutral community model and null model revealed that the relative importance of deterministic and stochastic processes in governing planktonic bacterial community assembly varies seasonally. Stochastic processes (dispersal limitation) are more prominent in spring, summer, and autumn, while deterministic processes (heterogeneous selection) play a greater role in winter. This study is essential for gaining a comprehensive understanding of the effects of water diversion projects and offers valuable references for the assessment of other similar projects.